Zinc enriched Pseudomonas fluorescens triggered defense response in rice against bacterial leaf blight - SHARMA, PRANAMIKA; BORA, LOHIT CHANDRA; NATH, PALASH DEV; ACHARJEE, SUMITA; BORA, POPY; VASANTRAO, JAGDALE MAHESH (The Indian Journal of Agricultural Sciences, 2020)
Bacterial leaf blight (BLB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is a major disease in rice and Pseudomonas fluorescens is known as a successful bioagent against the pathogen. The present investigation was carried out to study the effect of micronutrients, viz. boron (B), iron (Fe), zinc (Zn), and molybdenum (Mo) on the efficacy of the bioagent and induction of defense mechanism in rice. The study revealed that P. fluorescens strain PfAs1 enriched with 50 ppm Zn could suppress the blight pathogen by 45.92% compared to control and other micronutrients under in-vitro condition. The results also demonstrated a reduction of 82.99% disease intensity in rice due to application of Zn enriched PfAs1. Further study was made to understand whether the Zn enriched PfAs1 (Zn PfAs1) induces defense response in rice. The levels of expression of defense related genes, viz. OSPR1a, OSPR1b, OSPR10a, Xa1 and Xa26 against Xoo was quantified by quantitative PCR (qPCR). During the interaction of rice with Zn PfAs1, a 20 fold increase in the expression of rice BLB resistance gene Xa26 and pathogenesis related (PR) gene OsPR1b, was observed when compared with controls. Similarly, 14 and 10 fold increase in levels of expression of OsPR1a and OsPR10a genes was recorded, respectively. An 8 fold increase in the level of expression of Xa1 gene was also recorded in the study. This is the first report on enhanced defense response in rice due to the antagonistic potential of Zn enriched P. fluorescens strain against BLB pathogen.